2017
DOI: 10.3390/toxins9100302
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Identification of Mycotoxigenic Fungi and Mycotoxins in Stored Wheat Grain

Abstract: This study aimed to assess the occurrence of toxigenic fungi and mycotoxin contamination in stored wheat grains by using advanced molecular and analytical techniques. A multiplex polymerase chain reaction (PCR) strategy was established for rapid identification of mycotoxigenic fungi, and an improved analytical method was developed for simultaneous multi-mycotoxin determination in wheat grains by liquid chromatography-tandem mass spectrometry (LC/MS/MS) without the need for any clean-up. The optimized multiplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 69 publications
1
61
0
2
Order By: Relevance
“…To detect and differentiate aflatoxigenic and non-toxigenic Aspergilli, several methods have been developed including molecular marker-based methods and fungal culture methods [19,20]. Currently, in most cases, aflatoxigenic fungi are being identified by culture methods coupled with thin layer chromatography (TLC) or high-performance liquid chromatography (HPLC).…”
Section: Introductionmentioning
confidence: 99%
“…To detect and differentiate aflatoxigenic and non-toxigenic Aspergilli, several methods have been developed including molecular marker-based methods and fungal culture methods [19,20]. Currently, in most cases, aflatoxigenic fungi are being identified by culture methods coupled with thin layer chromatography (TLC) or high-performance liquid chromatography (HPLC).…”
Section: Introductionmentioning
confidence: 99%
“…Following the multiplex PCR assay with the primer pairs: nor-1, ver-1, omt-A, and aflR1 sequences, the results indicated that the DNA from Aspergillus flavus (4) and Aspergillus parasiticus(1) [AF4 and AP1] possessed all the four aflatoxin biosynthesis genes. A number of researchers have made similar reports on different agricultural and food products (Nwachukwu et al, 2019;Sadhasivam et al, 2017;Gherbawy et al, 2016;Degola et al, 2007). The DNA of AF2 and AF3 indicated positive reaction for the following genes: nor-1 gene, ver-1 gene and aflR gene.…”
Section: Discussionmentioning
confidence: 88%
“…A multiplex polymerase chain reaction (PCR) strategy was established for rapid identification of mycotoxigenic fungi (Sadhasivam et al, 2017). The RT-PCR results obtained with genomic DNA as a template indicated that all tested aflatoxigenic isolates expressed nor-1 gene with significant expression levels in chicken products.…”
Section: Expression Of Nor-1 Gene Of Aflatoxins and Ocra Gene Of Ochrmentioning
confidence: 99%